Providing education for the community to improve nutrition for toddlers - Suprapto, Suprapto; Arda, Darmi; Tri Wijayanti, Yoga; Fredy Saputra, M. Khalid (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2025)
Good nutrition in toddlers is an important factor in supporting children's optimal growth and development. However, there are still many people who have a lack of understanding of good nutritional parenting, which can have an impact on the risk of stunting and other nutritional problems. The Community Service Program (PkM) aims to increase public knowledge about the importance of balanced nutrition and healthy diets for children, especially mothers under five. The methods used in this program include education through counseling, demonstrations of making healthy menus, and interactive discussion sessions. This program was attended by 50 mothers under five in the Posyandu assisted area. The evaluation results showed a significant increase in participants' understanding of nutrition for toddlers, which was demonstrated by an increase in pre-test and post-test scores. In addition, there has been a change in the practice of feeding toddlers, with more mothers adopting a healthy diet after attending education. In conclusion, community-based nutrition education effectively increases the understanding and practice of balanced nutrition for toddlers, which is expected to contribute to reducing stunting and malnutrition rates